Proceedings of the International Symposium on Mechanical Engineering and Material Science 2016
DOI: 10.2991/ismems-16.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis and Experimental Verification Based on Design Parameter Variation of Vacuum-Insulated Pipe for Cryogenics

Abstract: Abstract. Since natural gas is mainly transported or supplied in a liquefied state under high pressure, BOG (boil off gas) is frequently generated due to the adiabatic relation outside the pipe. To reduce BOG, various studies are being conducted. Recently, vacuum-insulated pipes are mainly used. Thus, in this study, temperature distribution in a vacuum-insulated pipe was observed through thermal analysis with the pipe type and diameter as design parameters. Additionally, thermal analysis was verified through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They found that a lower filling rate resulted in a higher proportion of vaporized liquid hydrogen and identified an interaction between the filling rate and the direction of gravity. Lee et al [7] conducted a thermal analysis and experiments on vacuum-insulated bellows and joint-type pipes to compare and verify the generation of BOG. The results from the analysis and experiments were in agreement within 5%.…”
Section: Introductionmentioning
confidence: 99%
“…They found that a lower filling rate resulted in a higher proportion of vaporized liquid hydrogen and identified an interaction between the filling rate and the direction of gravity. Lee et al [7] conducted a thermal analysis and experiments on vacuum-insulated bellows and joint-type pipes to compare and verify the generation of BOG. The results from the analysis and experiments were in agreement within 5%.…”
Section: Introductionmentioning
confidence: 99%